Peran Suster Alma Dalam Berkatekese Bagi Penyandang Disabilitas di Komunitas Bhakti Luhur - Hamat, Yulianus Evantus; Meo, Yohanes Wilson B. Lena; Handoko, Petrus Maria (Jurnal Masalah Pastoral, 2024)
The main focus of this paper is to describe the role of the Alma nuns in providing religious instruction to children with disabilities. The purpose of this paper is to explore the ways and strategies used by the Alma nuns in providing catechesis to children with special needs. The method used is qualitative, namely literature study and direct interviews with the Alma nuns and nurses working in the Bhakti Luhur community. This method helped the author in knowing and understanding the concrete steps taken by the Alma nuns as well as the challenges they experience in providing religious instruction. The study found that the Alma nuns truly dedicate themselves and their energy in caring for, nurturing and teaching religious education to children with disabilities. The methods they use in helping the children to grasp the teaching given are using sign language, communication through photos and videos, combining the senses of sight, hearing, smell, taste and various positive stimuli that help children to grasp the learning given. It is hoped that this article will provide readers with new insights into the role of the Alma nuns in helping children with disabilities understand their religion and faith as children of God. This article seeks to answer the question; What is the role of the Alma nuns in providing catechesis to people with disabilities?